Theory and practice of state regulation and support of small and middle entrepreneurship subjects - A. V. Nurmukhametov (Russian Journal of Economics and Law)
Objective: to analyze the applied measures of support of small and middle entrepreneurship subjects in the economically developed countries with a view of their application in Russia. Methods: statistical, abstract-logical method, observation. Results: Revealed the efficient measures of state support of the small and middle entrepreneurship subjects, among which are: development of infrastructural services, creating favorable conditions for business, system of state guarantees for credits, cooperation between large and small business, etc. Basing on the studied experience, methods are proposed, which can be used in Russia. Scientific novelty: Basing on the analysis of the foreign practice of state regulation and support of small and middle entrepreneurship subjects, the author views the practice of developed countries and highlights the most efficient measures for Russia to solve the problems of the small and middle entrepreneurship subjects support. The synergy model is viewed, which can be efficient with the use of outsourcing system. Practical value: Measures are proposed which can help when solving the problem of state regulation and support of small and middle entrepreneurship subjects.